تقييم واقع الفحوم الهيدروجينية البترولية في بعض الكائنات البحرية والمياه الشاطئية لمدينة جبلة (Latakia University Journal -Basic Sciences Series, 2018)
نبين في هذه الدراسة توزع الفحوم الهيدروجينية البترولية في المياه الشاطئية لمدينة جبلة خلال الفترة الممتدة ما بين (2000-2001), وفي أنسجة بعض أنواع السمك المحلي التي تم جمعها خلال الفترة السابقة من شاطئ مدينة جبلة, وهذه الأنواع هي: (بوري Chelon sp., زليق Sparisoma sp., منوري Olada sp., غريبة Sigonus sp., إسفنج Balistes sp., نايلون Sargocentron sp., عروسة البحر Coris sp.). تراوحت تراكيز الفحوم الهيدروجينية البترولية في المياه المدروسة ما بين (0.162-1.955µg/l)، وقد احتوت  (66 %)من العينات المدروسة والبالغ عددها (27) عينة على تركيز أقل من (1µg/l). تشير هذه الدراسة إلى انخفاض مستوى التلوث بالفحوم الهيدروجينية البترولية في المياه المدروسة مقارنة مع مناطق شاطئية أخرى من البحر المتوسط. وتبين المعالجة الإحصائية للبيانات التي تم الحصول عليها أن تركيز هذه الملوثات في المياه المدروسة يتعلق بعوامل أهمها وجود روافد خارجية تحمل معها مياه الصرف الصحي لبعض المنشآت الصناعية والخدمية والتجمعات السكانية والتي تصب في مياه البحر. كما تراوحت تراكيز الفحوم الهيدروجينية البترولية في أنواع السمك المدروسة بين قيم دون عتبة الكشف (not detected) و(0,367µg/g dry wt)، وقد سجلت أعلى التراكيز في أنسجة النوعين "غريبة وبوري" والتي بلغت 0.367µg/g) و(0.219µg/g على الترتيب. This study shows the distribution of petroleum hydrocarbons in Jableh tidal waters during 2000-2001,and in the tissues of some local fish spices which have been collected from Jableh coast during that period. It includes:( Chelon sp., Sparisoma sp., Olada sp., Sigonus sp., Sargocetron sp., and Coris sp.). Concentration of petroleum hydrocarbons in these waters ranged between (0.162-1.955 µg/l). Sixty-six percent of the twenty-five samples which counted contained less than   (1 µg/l). This study shows that the level of petroleum hydrocarbons pollution in these waters is low when compared with other coastal regions of the Mediterranean. The statistical treatment of data collected shows that the concentration of these pollutants in these waters is associated with a variety of factors, the most of which is external sources that carry sewage from some industrial establishment that ends at the sea. The concentration of petroleum hydrocarbons in the studied fish spices ranged between   (not detected) and (0.367 µ/g dry wt.), the highest concentration has been registered in tissues relating to Chelon sp.  And   Sigonus sp. and reached (0.219 µg/g and 3.367 µg/g) respectively.